The Local Knowledge and Use of Plants In The Kenduri Sko Traditional Ceremony In The Community Of Hamparan Rawang District, Sungai Penuh City, Jambi Province, Indonesia - Marsanda, Firda Dwi; Adriadi, Ade; Witono, Joko Ridho (Universitas Jambi, 2024)
The Kenduri Sko Traditional Ceremony is an ancestral tradition passed down by ancestors, characterized by the conferment of traditional titles and the cleansing of heirloom objects. In the Kenduri Sko ceremony, plants are used as symbols and for purifying heirloom objects. This study aims to identify the types of plants used in the Kenduri Sko ceremony, determine their Use Value and Plant Part Value. The research was conducted from February to July 2024. The findings reveal that there are 16 species of plants from 10 families used in the Kenduri Sko ceremony in the Hamparan Rawang district, with the highest Use Value being 1 and the most utilized plant part being leaves (38%).